Higher education, emerging technologies, and community partnerships concepts, models and practices - Bowdon, Melody A.; Carpenter, Russell G. (Information Science Reference, 2011)
"This book is a comprehensive collection of research with an emphasis on emerging technologies, community value, and corporate partnerships, providing strategies to implement partnerships" - Provided by publisher
Includes bibliographical references
Keywords: Education, Higher / Effect of technological innovations on; Distance education / Computer-assisted instruction; Educational technology; Community education / United States; Computerunterstützter Unterricht; Hochschulbildung; USA; Aufsatzsammlung